Ethopoiésis e Heavy Metal: Subjetivação e consumo na cena de Natal-RN - Messias, Jessica da Silveira (2013)
Our research intends to comprehend the configuration of the resistance (Foucault) as the stylization of life in the contemporary world, taking Heavy Metal as the specific object of study. We believe that Heavy Metal is an ethopoietical device which admits practices of freedom withstanding the reified moral habits since the beginning of the socialization. This is reflected, mainly, in the creation of new individual and communal ways to stylize the life. We also suggest an expansion of Foucault s concept of resistance, considering the idea of consumer society described by Zygmunt Bauman. Our hypothesis understands that the contact with the underground of Heavy Metal provides new ethical manners (Foucault), where the individual take the Heavy Metal as a way of life. At this point, the consumption becomes a key-word since the participation in the underground of Heavy Metal is a way of consumption out of the rules of marketing a practice of freedom, a way of particular existence , being different in both mode and duration